Market structure and performance of Malaysian banking industry. Issue 2 (3rd October 2016) - Ab-Rahim, Rossazana; Chiang, Sheen Nie
Abstract : Purpose: The main purpose of this paper is to examine the relationship between the market structure and financial performance of Malaysian commercial banks over the period of 2000 to 2011 by testing the structure-conduct-performance (SCP) and efficient-structure (ESH) hypotheses. Design/methodology/approach: Data envelopment analysis (DEA) is employed to measure the efficiency of banks, while concentration ratio is used to assess the market structure of Malaysian banks. Next, utilizing the least squares method, both variables – market structure and efficiency of banks – among other explanatory variables (market share, operating expenses, loans ratio and size of banks) are regressed upon the dependent variable, namely financial performance of banks represented by return on asset (ROA), return on equity (ROE) and net interest margin (NIMTA). Findings: The concentration of Malaysian banking industry is at a declining trend; structurally speaking, Malaysian banks are more competitive due to less market concentration. In terms of efficiency, the DEA results reveal that Malaysian banks are operating below their capacity at 40 per cent of efficiency. Thus, Malaysian banks could reduce their utilization of inputs by 60 per cent to operate on the efficient frontier. Next, the results offer support to ESH, which implies that market concentration and banking efficiency determines the profitability performance of Malaysian commercial banks. Originality/value: Past studies on Malaysian banking sector had tended to focus either on measuring the performance or assessing the market structure of banks. Thus, this study attempts to fill the gap in the literature by testing the nexus between the market structure and the performance of banks.